Community public health safety emergency management and nursing insurance service optimization for digital healthy urban environment construction - Hu, Guosheng; Wang, Zeyu; Jiang, Shaoxiang; Tian, Yuan; Deng, Yue; Liu, Yang (Frontiers in Public Health, 2022)
It is urgent to promote the construction of healthy digital cities and improve the living standards of urban residents. This paper studies community public health safety emergency management and nursing insurance service optimization methods for healthy urban environment construction based on the analysis of healthy cities. Firstly, the concept of digital healthy urban environment construction is discussed. Secondly, the role of environmental health is discussed. Finally, two methods are designed to study the emergency management of public health safety and nursing insurance services in urban communities under the condition of environmental health. The results show that X1 and X6 in the city’s environmental health score have relatively low scores between 2016 and 2018, below 0.5. The scores for the remaining three years are relatively high, above 0.5. Meanwhile, residents are very satisfied with the information collection and management in public health and safety emergency management. The number of very satisfied people is more than 40%. Residents are very satisfied with resource allocation and privacy management. The number of very satisfied people is above 30%. Residents’ satisfaction with risk perception and management measures is low. The number of very satisfied people is below 20%. This paper not only provides a reference for the construction and improvement of a healthy digital city but also contributes to improving the healthy life of urban residents.